2013
DOI: 10.1007/978-3-642-31546-6_5
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Characterization of the Requests to Wikipedia

Abstract: This paper presents an empirical study about the temporal patterns characterizing the requests submitted by users to Wikipedia. The study is based on the analysis of the log lines registered by the Wikimedia Foundation Squid servers after having sent the appropriate content in response to users' requests. The analysis has been conducted regarding the ten most visited editions of Wikipedia and has involved more than 14,000 million log lines corresponding to the traffic of the entire year 2009. The conducted met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
3
1
0
Order By: Relevance
“…In [112], it is shown that WP is mostly edited between 1 pm and 11 pm, almost in a universal manner for all language editions. This is in accord with the results in [76,47]. Deviations from this universality originates from cultural differences and working habits, such that language editions with more editors from countries with longer working hours, are even more edited in later time in evening and around midnight.…”
Section: Time Of Editingsupporting
confidence: 87%
See 1 more Smart Citation
“…In [112], it is shown that WP is mostly edited between 1 pm and 11 pm, almost in a universal manner for all language editions. This is in accord with the results in [76,47]. Deviations from this universality originates from cultural differences and working habits, such that language editions with more editors from countries with longer working hours, are even more edited in later time in evening and around midnight.…”
Section: Time Of Editingsupporting
confidence: 87%
“…For example, German, English, Spanish, and Italian WPs are mostly edited during the working days, in contrast to Japanese, Korean, and Chinese WPs being mostly edited on weekends. Our findings are in accord with [76] but in contrast with [47]. However, the latter work studied a sample of four languages only and a shorter monitoring time, and we believe that these lead to the conclusion that editorial activity in WP "while showing a clear diurnal pattern, do not have a clear weekday-weekend pattern.…”
Section: (B)supporting
confidence: 72%
“…Infrastructure optimization. As observed in previous work (Reinoso et al 2012), these findings are valuable for optimizing the Wikimedia infrastructure. Given the scale of Wikipedia, optimizing data caching and load-balancing to reflect the actual needs of the consumers across space and time can offer significant benefits for the platform's performance.…”
Section: Discussionsupporting
confidence: 77%
“…Previous studies describe how consumption patterns reveal information about seasonal fluctuations in mood (Dzogang, Lansdall-Welfare, and Cristianini 2016) at the population scale and how editors' temporal patterns exhibit culturespecific differences . It has also been noted that modeling Wikipedia temporal readers' needs has implications for technical improvements and could be exploited to develop scalable infrastructure adapted to reading patterns (Reinoso et al 2012).…”
Section: Related Workmentioning
confidence: 99%